2019
DOI: 10.22435/hsr.v21i4.930
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Hidup Bersih Dan Sehat Santri Putri Pesantren X Yogyakarta

Abstract: Pesantren X, a place for female Islamic student’s living in from many districts in Indonesia, has a lot of health issues both personal hygiene and environmental health. Room sanitation as a part of wide environment at Pesantren X was determined by student’s daily activity and their behaviours from one to another. This study aims to identify the conditions of female student’s room as well as their behaviour. This is a qualitative study. The data were collected by in-depth interviews with fi ve female Islamic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
3
Order By: Relevance
“…This statement showed that the relationship between the work of parents and gender was mutually debilitating (Sarwono, 2010); moreover, there was no interaction between gender and parental work on environmental literacy. It happened because whatever the work of parents, either civil or non-civil servant, they had the opportunity to provide the same environmental literacy education to their children, both boys and girls (Machfutra, et al, 2018). However, when looked at environmental literacy from the gender aspect, it was no need to look at the background of the parents, namely their work or vice versa because it would be weakening each other and have no effect.…”
Section: Corrected Total 1738871 69mentioning
confidence: 99%
“…This statement showed that the relationship between the work of parents and gender was mutually debilitating (Sarwono, 2010); moreover, there was no interaction between gender and parental work on environmental literacy. It happened because whatever the work of parents, either civil or non-civil servant, they had the opportunity to provide the same environmental literacy education to their children, both boys and girls (Machfutra, et al, 2018). However, when looked at environmental literacy from the gender aspect, it was no need to look at the background of the parents, namely their work or vice versa because it would be weakening each other and have no effect.…”
Section: Corrected Total 1738871 69mentioning
confidence: 99%
“…Santriwati dituntut untuk beradaptasi dengan kegiatan dan peraturan di pesantren dengan jadwal padat yang harus diikuti santri. Dalam kegiatan pendidikan formal, peserta didik hanya belajar dan berinteraksi dengan teman serta guru kurang lebih 6-7 jam dalam satu hari, hampir 24 jam remaja berinteraksi dengan teman sebayanya di lingkungan pesantren (Machfutra, 2018). Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang mempengaruhi kebersihan diri selama menstruasi pada remaja putri di Pondok Pesantren Nurul Islam Bungo.…”
Section: Latar Belakangunclassified
“…Dewi, 2020;M. Dewi, Ulfah, Fatmawati, & ..., 2018;Fadilah, Triyani, & Hikmawati, 2020;Febrianti, 2020;Hadi, 2018;Khafid, Ainiyah, & ..., 2019;Khairunisa, 2019;Machfutra, Noor, Asropi, & ..., 2018;Makful & Pirawati, 2019;Masita, 2019;Muthmainnah & ..., 2020;Nadrati, Wijayanto, & ..., 2019;Nikmah, 2018;Noveyani, Marchianti, & ..., 2020;Rif'ah, 2019;Sari, 2018;Sembel, Mambu, Manuruh, & ..., 2018;Tobroni & Habibi, 2020;Wahyudin & Setiaman, 2019) Kementerian Agama bekerjasama dengan ormas Islam telah menyelenggarakan peringatan Hari Santri 2020 bertema 'Santri Sehat Indonesia Kuat' yang diluncurkan pada 1 Oktober 2020. Peringatan Hari Santri tahun ini dilakukan dengan menerapkan protokol kesehatan untuk mencegah penularan dan penyebaran Covid-19.…”
Section: Pendahuluanunclassified